Cloning of xylanase gene from Trichoderma reesei ATCC 58350 - Mohamad Fuzi, Siti Fatimah Zaharah; Md. Illias, Rosli (2007)
Gene encoding Xylanase from Trichoderma Reesei ATCC 58350 was amplified using Polymerase Chain Reaction. Both genomic and cDNA of the xylanase gene were obtained and analysed. Comparison of nucleotide sequence shows the existence of one intron. Amino acid sequence compariosn with other xylanase exhibited 100% identities to xylanase from Hypocrea jecorina QM6a.